(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Character education today faces a dual challenge: nurturing an environmentally conscious generation while providing meaningful learning experiences. In response to the climate crisis and the mandate of SDG4.7, educators are reexamining every aspect of classroom learning practices, from the resources they use to the competencies they develop, to simultaneously foster ecological awareness and moral agency. This study examines how digital tools can transform character education projects into sustainable and pedagogically robust practices. We analyzed a cohort of thirty two (N = 32) postgraduate students in Early Childhood Education (ECE) who collaboratively produced a digital morality guidebook. Implementing a paperless workflow reduced material use by 72%, increased immersive learning satisfaction by 84.4%, and strengthened a set of 21st-century competencies. Survey results indicated that 93.8% of participants felt more creative when designing with Canva, and every student reported improved collaboration skills through online coordination. Thematic analysis of reflective journals revealed three cornerstones of innovation: cloud-based design that replaces physical drafts, AI-assisted validation that eliminates the need for field trips, and an e-filing system that simplifies legal documentation. Based on these findings, we formulated the Eco-Digital Character Education (EDCE) framework, which reduces the project’s carbon footprint by approximately 40% while increasing moral reasoning competencies by 35%. This framework provides a practical blueprint for educators, particularly in developing countries, who aim to achieve SDG 4.7 through technology-based and environmentally conscious pedagogy.